From Enemies to Allies: the Mystery of Prince Oleg’s Campaign against Constantinople - Romensky, Aleksandr A. (Studia Ceranea, 2021)
This article proposes a rethinking of the main patterns of Rus-Byzantine relations at the turn of the 9th–10th centuries. The Christianization of some groups of Rus’ elite after 860 seems to be plausible, but short-lived. The crisis in relations with Khazaria prompted a search for new trade privileges in Byzantium. The so-called Oleg’s campaign on Constantinople was nothing other than his joining the military service. During the constant struggle with Arabs, the Empire needed to receive new military forces from Rus’. Possibly the recruitments were accompanied by a provocative demonstration of strength. This action was rethought in Rus’ian chronicle writing as the great victory of “Oleg the Prophet”. The joining of Rus’ troops to the Byzantine navy occurred no later than 906, when logothetes Himerios was able to defeat the Muslims. The Rus-Byzantine treaty of 911 strengthened the partnership and fostered the baptism of some Rus mercenaries.